Sistemas municipais de ensino e o instituto Ayrton Senna na Amazônia paraense - Miléo, Irlanda do Socorro de Oliveira (2013)
This investigation aimed in discuss the Third Sector role and its partnerships established in public Brazilian education by introducing it as a study object with Instituto Ayrton Senna and Prefeituras Municipais de Altamira and Santarém, cities located in the west side of Amazônia Paraense, at Programa Rede Vencer and its subprograms. The research had the objective of revealing whether the Programa Rede Vencer proposed by IAS has really contributed in what it is proposed to: evolve quality at education in these provinces. In order to reply to such issue we have elected as a general objective to analyze the unfolding effects of Programa Rede Vencer develops in the provinces of Altamira and Santarém as well as its possible implications in the improvement of municipal education quality and the basis date is from 2007 up to 2011. Research took place from specialized literature contributions about outsourcing, curriculum polices and quality at education. Educational context has been verified from statistic dimensions regarding flow indicators data and its performance, as well as financial data regarding federal resources transferences and qualitative dimensions through management team participation, teachers and parents or those responsible for municipal education. The study has clarified that even though performance in fee improvements were shown and also the performance indicators observed in two researched education institutes also improved, education standardizing remain still having issues about disapproval and distortion regarding age versus year in school, mainly in schools located in the countryside. Nevertheless, improvements verified in such index cannot be accredited only to management actions developed by SEMED Institute in follow up and monitoring education instruments but they should be accredited in regard to public resource investments and the federal government actions through financial assistance politics were responsible for enabling and maintaining strategic actions that promotes quality at education. Investigations pointed out that quality concept presented by IAS through educational programs is based upon two pillars: learning and performance results by clarifying broad perspective regarding quantity matters as it is supported the idea of performance indicators as well as competence matrix and abilities as excellence instruments to improve teaching. It has been concluded that even though there is the introduction of management administration and the curriculum restructuring conducted by IAS in Altamira and Santarém regions, they demonstrate to be not efficient in two issues: the non-accomplishment of all goals about Partnership Instrument agreed in the past as its efficiency happens way more in the operational matter (follow up and education monitoring) rather than turning the management team into an instrument to diagnose issues and also rather than really solving these issues the main objective. The implementation of management techniques conduct to the expected results which are contrary to democratic values and principles. A new aspect to be considered is the conquering of an active consent by teachers and the management teams which highlights politics strength and discourse technique of the Institute. In such sense, the greatest efficiency consists of promoting instrument quality in education through management language and also in performance matters wich induces a dependency of educational management on "manufactured quality" matters through success indicator